2001
DOI: 10.1074/jbc.m104408200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor 90 Is a Substrate and Regulator of the Eukaryotic Initiation Factor 2 Kinase Double-stranded RNA-activated Protein Kinase

Abstract: Nuclear factor 90 (NF90) is a member of an expanding family of double-stranded (ds) RNA-binding proteins thought to be involved in gene expression. Originally identified in complex with nuclear factor 45 (NF45) as a sequence-specific DNA-binding protein, NF90 contains two double stranded RNA-binding motifs (dsRBMs) and interacts with highly structured RNAs as well as the dsRNA-activated protein kinase, PKR. In this report, we characterize the biochemical interactions between these two dsRBM containing proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 45 publications
6
90
0
Order By: Relevance
“…NF90 is one of the evolutionarily conserved members of the dsRNA-binding protein family and is expressed abundantly in various human cells. Previous studies (6,7,9,10,13,40) identified and confirmed PKR as the key interacting partner for NF90 in cells, in addition to its function in regulating IL-2 gene expression in T cells (4). PKR plays an important role in mediating innate immunity to viral infection and is required for NF90 antiviral activity, as demonstrated in a vesicular stomatitis virus infection experiment using PKR-knockout (PKR…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…NF90 is one of the evolutionarily conserved members of the dsRNA-binding protein family and is expressed abundantly in various human cells. Previous studies (6,7,9,10,13,40) identified and confirmed PKR as the key interacting partner for NF90 in cells, in addition to its function in regulating IL-2 gene expression in T cells (4). PKR plays an important role in mediating innate immunity to viral infection and is required for NF90 antiviral activity, as demonstrated in a vesicular stomatitis virus infection experiment using PKR-knockout (PKR…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that binding of either dsRNA or PACT to PKR may interrupt intramolecular interaction between the kinase and dsRNA-binding domains, leading to an open conformation of the PKR molecule and allowing autophosphorylation to occur (49). NF90 is phosphorylated by PKR in its RBD (6). Previous studies (7,9,29) showed that NF90 interacts with PKR in the yeast two-hybrid and GST-pull down assays.…”
Section: /2mentioning
confidence: 99%
See 3 more Smart Citations